Singapore's ticking market : the watch industry's thought leader - Pereira, Manesha (2017)
When it comes to the world of watches, a tiny city state like Singapore holds its own against heavyweights from the West and the Middle East. But unlike those countries, Singapore doesn't have the numbers. What it does have however is the potential to be a thought leader, governing over what stays and what goes in the international economy of timepieces. Singapore is a force to be reckoned with, a leader to whom the globe looks up to for current trends and fashion in watches. The collectors and enthusiasts that she houses are a tier above the rest. They are risk takers, proponents for the horological avant garde and shun normalcy. Here in Singapore new business models are disrupting the watch economy and changing the way the market works. She has earned her title as a thought leader producing some of the world’s best collectors, retailers and bloggers to whom the entire industry relies on. Stagnancy is not an option for a thought leader.